Desenvolvimento de podcast como recurso educacional para pessoas com estomias intestinais - Nascimento, Rafael Moreira do (2023)
People with stomas are those undergoing a surgical procedure whose objective is to exteriorize a part of the digestive, respiratory or urinary system, through an artificial opening that allows the communication of the internal organ with the external environment for the maintenance of life. The Ministry of Health published Ordinance GM/SAS/MS nº 400/2009, providing the National Guidelines for the Health Care of People with Ostomies within the scope of the Unified Health System (SUS). Among the attributions, it defines that the health care of people with a stoma is composed of health education actions. Thus, podcasts are digital audio files available on internet platforms whose purpose is the transmission of information, and when properly applied they can be considered an innovative alternative for educational practice. With this, the objective of the study was to develop and validate an educational podcast for people with intestinal stomas. This is a methodological study carried out from January 2022 to March 2023, divided into four phases: (1) Analysis of podcast productions; (2) Construction of the educational podcast; (3) Validation of podcast content; and (4) Recording and publishing the podcast. The analysis of the data collected through the content validation instrument, via Google Forms, was carried out considering the Content Validity Index (CVI). The minimum acceptable agreement index among the study judges for each item was 0.78, and for the instrument in general it was 0.80. The collected data were compiled and analyzed in spreadsheets with the help of the Microsoft Office Excel® 2016 program and the results presented in the format of charts and tables. The study was carried out based on ethical principles respecting Resolution No. 466 of 2012 of the National Council for Ethics in Research involving human beings, considered by the Research Ethics Committee of the Federal University of Rio Grande, with favorable opinion No. 5,521,293 and CAAE 59714122.8.0000.5537. In the first phase of the study, an article was found that dealt with podcasts for people with intestinal stomas in the literature, on music platforms 14 podcasts and 109 episodes, with prevalence on spotify, English language, in the interview format. For the development of the podcast, two educational scripts were prepared referring to the episodes of the channel, such as episode I: “care with the intestinal ostomy, peristomal skin and possible complications” and episode II: “care with hygiene, emptying and changing clothes”. intestinal ostomy collection bags”. Podcast content had an overall CVI of 0.89 for episode I and an overall CVI of 0.97 for episode II. After the content validation and adaptation stage, the podcast was titled “EstomaCast”, recorded and made available free of charge on Spotify and Deezer, lasting approximately 30 minutes each. In this way, the contents of the podcast scripts were considered valid for recording the episodes, demonstrating that the material constructed for the technology is reliable and is adequate for use as an educational resource, with the aim of promoting selfcare for people with intestinal stomas. and consequently the adaptation of these subjects to this context.